The link between X-ray complexity and optical lines in NLS1s - Vietri A.; Berton M.; Ciroi S.; Congiu E.; la Mura G.; Cracco V.; Frezzato M.; Chen S.; Cattapan A.; Peruzzi T.; Rafanelli P. (Italy, 2026)
Narrow-line Seyfert 1 galaxies (NLS1s) are a subclass of active galactic nuclei (AGN). It is often believed that these AGN have small black hole mass, which is responsible for the narrowness of the permitted lines. They are also characterised by a high accretion rate, typically closer to the Eddington limit. Nevertheless, narrow permitted lines might also be caused by a disk-like broad-line region (BLR) viewed pole-on. This class of objects presents strong X-ray emission, which is characterised by a very steep spectral index described by a single power law. In particular, some of them exhibit particular features around the iron K-shell energy at 6-8 keV. Recently, this different spectral behaviour was attributed to inclination. In this work we are going to analyse optical spectra to measure in different ways the width of Hβ, which is another potential inclination indicator. Our aim is to search for a correlation between the high-energy spectral complexity and FWHM of Hβ, in order to verify whether or not the broad-line region could be flattened.